Verschiedene sprichwörtliche Redensarten – the First Croatian Phraseological Dictionary - Kovačević, Barbara; Štebih Golub, Barbara (Kalbotyra, 2020)
The first Croatian phraseological dictionary, compiled in German under the title Verschiedene sprichwörtliche Redensarten was published as a part of the conversational manual accompanying the last published grammar of the Kajkavian literary language, Grammatik der kroatischen Mundart. Its author, Ignac Kristijanović, had accomplished this pioneering undertaking against the contemporary practice, listing the idioms as separate phraseological units in form of a small phraseological dictionary, and not within the dictionary entries of the general dictionary. The paper deals with the macro- and microstructure of Kristijanović’s dictionary within the theoretical framework of the so-called Zagreb School of Phraseology (Menac, Fink-Arsovski). On the macrostructural level, the analysis focuses on the selection principles of the included units and their order in the dictionary. Special attention is paid to the question which material is included, ie. whether the dictionary contains only idioms defined in accordance with today’s phraseological theory and whether the author makes a distinction between idioms and other fixed multi-word expressions (collocations, proverbs). On the microstructural level, it is being examined which form of a idiom is taken as a lemma and how the Kajkavian idioms are translated on the German side of the dictionary (an equivalent German idiom; a German idiom and the explanation of its meaning; the description of the situation in which the idiom is being used). In addition, the question of dealing with synonymous idioms is discussed. In spite of a sporadically non-systematic treatment of structurally similar idioms as dictionary units, and taking into consideration that the Verschiedene sprichwörtliche Redensarten was compiled in the first half of the 19th century, Kristijanović’s dictionary can be viewed as an interesting and valuable contribution to Croatian and Slavic phraseology and phraseography.